A therapeutic role of exosomal lncRNA H19 from adipose mesenchymal stem cells in cutaneous wound healing by triggering macrophage M2 polarization. (May 2023) - Li, Bo; Qian, Li; Pi, Li; Meng, Xianxi
Abstract: Background: Emerging evidence has figured out that adipose mesenchymal stem cells (ADSCs) promote wound healing. Exosomes, which act as main paracrine factors and contains various protein, lncRNA, and miRNAs, play a critical role in wound healing. Nevertheless, the mechanism remains to be elucidated. This study aims to identify the underlying mechanism of ADSCs-derived exosome (ADSCs-exos)-mediated wound healing. Methods: ADSCs-exos were characterized using the transmission electron microscope, dynamic light scattering, and western blot. ELISA, RT-qPCR, flow cytometry, western blot, CCK-8 assay, transwell assay and tube formation were employed to validate the actions of ADSCs-exos harboring H19 in cell polarization, proliferation, migration and angiogenesis. The regulatory axis among H19, miR-130b-3p and PPARγ or STAT3 was confirmed by RNA pull-down, RIP assay and dual-luciferase reporter assays. Results: ADSCs-exos harboring H19 promoted macrophage M2 polarization, thereby enhancing fibroblast proliferation, migration and endothelial cell angiogenesis. However, their promotive effects were disrupted within H19 depletion in ADSCs-exos. Additionally, miR-130b-3p, directly targeting PPARγ or STAT3, was identified to be a downstream effector to participate in H19-mediated biological effects. Moreover, ADSCs-exos carrying H19 modulated cutaneous wound healing via H19/miR-130b-3p -mediated macrophage M2 polarization in vivo . Conclusion: Collectively, ADSCs-derived exosomal H19 accelerates cutaneous wound healing via the miR-130b-3p/PPARγ/STAT3 axis, indicating potential therapeutic strategies for the treatment of wound healing.